AN ANALYSIS OF FLOUTING MAXIM IN SCHIZOPHRENIC CHARACTER FOUND IN BEAUTIFUL MIND MOVIE - Aris Hidayatulloh; Abdul Ayiz (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2024)
Conversational implicature was proposed by Grice (1989) into four maxims. Those are: 1) quantity maxim, 2) quality maxim, 3) relation maxim, and 4) manner maxim. It is affects in the communication in society. It is also occurred in the communicative impairment. One of the phenomena is on the schizophrenia which affect on the deficit pragmatic and the ability to comprehend the implied meaning. The data of this research is from the representative utterances from John Nash which deals with something the speaker believes. The reason in specify the data is due to the limitation of this research in order to get more details about the pattern of the implicature in the believe of schizophrenic character. The data is classified into the classification by Searle and Vanderveken which is concentrated in the representative speech act before analysing it in implicature. The theory by Grice about the four maxims is used in this research to know about the conversational implicature by the main character who is diagnosed with schizophrenia. The results shows that most dominant flouting maxim is on the relation maxim. 13 chosen data which deals with the floating maxim shows the result as follows: 3 data in quantity maxim; 1 datum in quality maxim; 6 data in relation maxim; and 3 data in manner maxim. In flouted quantity maxim utterances do not deliver well in the conversation due to schizophrenia. It deals with the ability from speaker to have in line in the topic. The flouting maxim in quantity maxim and manner maxim has the same percentage. From flouting quantity maxim, Nash does over utterance in delivering the message so that the hearers do not understand what Nash mean. The flouted manner maxim indicates the inability of the speaker in delivering in a good manner and has a sufficient meaning in the utterance. While the fluted quality maxim does not affect to the conversation.